Addressing pollination deficits in orchard crops through habitat management for wild pollinators. Issue 1 (30th November 2022) - Garratt, Michael P. D.; O'Connor, Rory S.; Carvell, Claire; Fountain, Michelle T.; Breeze, Tom D.; Pywell, Richard; Redhead, John W.; Kinneen, Lois; Mitschunas, Nadine; Truslove, Louise; Xavier e Silva, Celina; Jenner, Nigel; et al.
Abstract: There is increasing evidence that farmers in many areas are achieving below maximum yields due to insufficient pollination. Practical and effective approaches are needed to maintain wild pollinator populations within agroecosystems so they can deliver critical pollination services that underpin crop production. We established nesting and wildflower habitat interventions in 24 UK apple orchards and measured effects on flower‐visiting insects and the pollination they provide, exploring how this was affected by landscape context. We quantified the extent of pollination deficits and assessed whether the management of wild pollinators can reduce deficits and deliver improved outcomes for growers over 3 years. Wildflower interventions increased solitary bee numbers visiting apple flowers by over 20%, but there was no effect of nesting interventions. Other pollinator groups were influenced by both local and landscape‐scale factors, with bumblebees and hoverflies responding to the relative proportion of semi‐natural habitat at larger spatial scales (1000 m), while honeybees and other flies responded at 500 m or less. By improving fruit number and quality, pollinators contributed more than £16 k per hectare. However, deficits (where maximum potential was not being reached due to a lack of pollination) were recorded and the extent of these varied across orchards, and from year to year, with a 22% deficit in output in the worst (equivalent to £14 k/ha) compared to less than 3% (equivalent to £2 k/ha) in the best year. Although no direct effect of our habitat interventions on deficits in gross output was observed, initial fruit set and seed set deficits were reduced by abundant bumblebees, and orchards with a greater abundance of solitary bees saw lower deficits in fruit size. The abundance of pollinators in apple orchards is influenced by different local and landscape factors that interact and vary between years. Consequently, pollination, and the extent of economic output deficits, also vary between orchards and years. We highlight how approaches, including establishing wildflower areas and optimizing the ratio of cropped and non‐cropped habitats can increase the abundance of key apple pollinators and improve outcomes for growers.